Preparation method of bentonite-containing composite material and application of bentonite-containing composite material in desertification control
By synergistically compounding bentonite with substances such as chitosan, sodium alginate, lignin and microbial metabolites extracellular polysaccharides, and adding plant fibers, montmorillonite powder and crosslinking agent glutaraldehyde to form stable chemical bonds and physical adsorption interactions, the problems of high cost in desert treatment, poor salt-resistant and thermal stability, low gel strength and short-lasting soil improvement effects in soil improvement are solved in the prior art, and efficient and long-lasting desert soil improvement and water retention effects are achieved.
Patent Information
- Application Number
- CN202411680719.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing bentonite-containing composite materials have problems such as high cost, poor salt-resistant and thermal stability, low gel strength and short-lasting soil improvement effects in desert management.
By synergistically compounding bentonite with substances such as chitosan, sodium alginate, lignin and microbial metabolites extracellular polysaccharides, and adding plant fibers, montmorillonite powder and crosslinking agent glutaraldehyde during the reaction, a stable chemical bond and physical adsorption interaction is formed, thereby generating a composite material with high gel strength and long-term water retention properties.
It significantly improves the gel strength and stability of the composite material, enhances its water retention performance and durability in desert environments and soil improvement effects, reduces costs, and solves the problems of poor salt resistance and insufficient thermal stability of traditional materials.
Smart Images

Figure CN119505924A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, in particular to a method for preparing a composite material containing bentonite and application of the composite material in desert control. Background Art
[0002] Desertification is one of the major ecological and environmental problems facing the world, which seriously threatens human survival and development. According to statistics, about one-third of the world's land area is suffering from desertification. The vast desert areas not only lead to a large waste of land resources, but also trigger a series of natural disasters such as sandstorms, which have a great negative impact on the ecosystem, agricultural production and residents' lives in the surrounding areas. Among the many measures for desert control, the research and development of efficient and suitable materials for desert environments is crucial. Traditional desert control materials have many limitations. For example, the highly absorbent resin commonly used in the early days has a certain water retention capacity, but it is expensive, has poor salt resistance, low gel strength and insufficient thermal stability, which makes it difficult for it to play a long-term and effective role in the complex and harsh environment of the desert. At the same time, its high cost also limits its large-scale application.
[0003] The existing technology has certain defects. First, the existing bentonite-containing composite materials have high costs, poor salt resistance and thermal stability, low gel strength, and the soil improvement effect is difficult to last. Secondly, the existing soil water-retaining materials have defects such as insufficient gel strength, poor water retention performance, and inability to improve soil fertility in the long term. Furthermore, the existing soil water-retaining materials have insufficient performance, low gel strength, and the soil improvement effect is not lasting, and nutrient supply is difficult to sustain. For this reason, we propose a method for preparing a bentonite-containing composite material and its application in desert control. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a composite material containing bentonite and its application in desert control.
[0005] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a method for preparing a composite material containing bentonite, the preparation method comprising the following specific steps:
[0006] Step 1, raw material preparation and pretreatment, select high-purity bentonite ore as the basic material, first grind the bentonite, activate the ground bentonite to improve its adsorption performance, soak the bentonite in a dilute hydrochloric acid solution and stir evenly, rinse repeatedly with clean water after stirring, and then put the activated bentonite into an oven for drying;
[0007] Select chitosan as a reactant, dissolve it in an acetic acid solution and mix it evenly for later use, collect the straw of plant fiber waste, wash it, dry it in the sun, and then crush it into powder for later use, select food-grade sodium alginate, dissolve it in warm water for later use, select montmorillonite powder and sieve it for later use, extract lignin from wood processing waste by alkaline extraction technology, soak it in a sodium hydroxide solution and stir it, filter it after soaking to obtain a filtrate containing lignin, add hydrochloric acid solution to the filtrate for acidification, filter and collect precipitated lignin after acidification, rinse it with clean water to neutrality, and then dry it for later use, cultivate Bacillus subtilis that can produce extracellular polysaccharides in LB medium, and collect the supernatant containing extracellular polysaccharides by centrifugation after the cultivation is completed;
[0008] Step 2, put all the bentonite into a reaction vessel with a stirring device, first add the dissolved chitosan solution, stir and mix until uniform during the addition process, ensure that the bentonite and chitosan are fully mixed, then add the prepared sodium alginate mixed solution, stir and mix until uniform during the addition process, ensure that the bentonite and sodium alginate are fully mixed, then add the purified lignin, stir and mix until uniform during the addition process, ensure that the bentonite and lignin are fully mixed;
[0009] Step 3: slowly add the plant fiber powder to the above-mentioned fully mixed reaction container, stir and mix until uniform during the addition process, ensure that the plant fiber powder is evenly dispersed in the system, and combine the plant fiber with the entire system. Subsequently, slowly add montmorillonite powder to the reaction container, stir and mix until uniform during the addition process, ensure that the montmorillonite powder is evenly dispersed in the system, and fully combine the montmorillonite powder with the entire system. Finally, slowly add the microbial metabolite extracellular polysaccharide solution to the reaction container, keep stirring during the addition process, and ensure that the extracellular polysaccharide is evenly dispersed in the industry system.
[0010] Step 4: under stirring conditions, add cross-linking agent glutaraldehyde dropwise to the reaction container. After the dropwise addition is completed, place the reaction container in a constant temperature water bath for water bath stirring to form stable chemical bonds between the components and enhance the gel strength and stability of the composite material. Under continuous stirring, slowly drop the mixed solution in the reaction container into a coagulation bath containing a calcium chloride solution. As the droplets gradually form gel beads in the coagulation bath, they are slowly fished out with a filter to avoid the gel beads from breaking. Then, a fermentation reaction is carried out. During the fermentation process, a series of complex chemical reactions will occur between the microbial metabolites and the bentonite and lignin, forming interactions such as chemical bonding and physical adsorption, thereby generating a composite water-retaining material.
[0011] Step 5: After the reaction is completed, the obtained composite material is repeatedly rinsed with deionized water to remove unreacted impurities and crosslinking agent residues, the rinsing liquid is discarded after rinsing, and the rinsed composite material is vacuum dried to obtain a bentonite-containing composite material.
[0012] As a further solution of the present invention: in the step 1, the bentonite is ground by grinding it in a ball mill for 4h-6h, with a rotation speed of 300r / min-500r / min, so that the particle size reaches 200-500 mesh, and the bentonite is activated by soaking the bentonite in a 10% dilute hydrochloric acid solution for 2h-3h and stirring continuously, then repeatedly rinsing with clean water until the pH value is 6.5-7.5, and then putting the activated bentonite into an oven and drying it at 60-80°C for 2h-3h for standby use.
[0013] As a further solution of the present invention: in the step 1, for chitosan, chitosan with a deacetylation degree of 80%-95% is selected, and it is dissolved in a 2%-5% acetic acid solution, and stirred at 100r / min-200r / min at room temperature until it is completely dissolved and then set aside;
[0014] Plant fiber waste straw needs to be crushed into 100-300 mesh powder for later use;
[0015] Sodium alginate is dissolved in warm water at a temperature of 40°C-50°C, with a mass ratio of sodium alginate to warm water of 1:10-15, and stirred at 150r / min-250r / min until dissolved and set aside;
[0016] Select montmorillonite powder with a purity of 90%-95%, sieve it to 100-300 mesh and set aside;
[0017] Soak the lignin in a 10%-15% sodium hydroxide solution at 80°C-90°C for 3h-5h with stirring, filter after the soaking to obtain a filtrate containing lignin, add 1 mol / L hydrochloric acid solution to the filtrate for acidification to reduce the pH value to 2-3, filter and collect the precipitated lignin, rinse with clean water until neutral, and then dry at 50°C-60°C for use;
[0018] Bacillus subtilis capable of producing extracellular polysaccharides is cultured in LB medium, and cultured in a shaking incubator at 30°C-37°C and 150r / min-200r / min for 24h-48h. After the culture is completed, the supernatant containing the extracellular polysaccharides is collected and used after centrifugation at 5000r / min-8000r / min for 10min-15min.
[0019] As a further scheme of the present invention: in the step 2, the chitosan solution is added in an amount according to a mass ratio of bentonite to chitosan solution of 1:2-4, and during the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30min-60min. The sodium alginate mixed solution is added in an amount according to a mass ratio of bentonite to sodium alginate of 2:3-5. During the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30min-60min. The lignin is added in an amount according to a mass ratio of bentonite to lignin of 3-5:2. During the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30-60 minutes.
[0020] As a further scheme of the present invention: in the step three, the amount of plant fiber powder added is 10%-15% of the total mass of the system, stirring is maintained during the addition process, the stirring speed is 150r / min-250r / min, and the stirring reaction is carried out for 30min-60min. The amount of montmorillonite powder added accounts for 15%-18% of the total mass of the system, stirring is continued during the addition process, the stirring speed is controlled to be 150r / min-250r / min, and stirring is continued for 30min-60min. The amount of extracellular polysaccharide added accounts for 20%-23% of the total mass of the system, stirring is continued during the addition process, the stirring speed is controlled to be 150r / min-250r / min, and the stirring reaction is carried out for 30min-60min.
[0021] As a further solution of the present invention: in the step 4, the amount of glutaraldehyde added is 1%-1.5% of the total mass of the system, the stirring speed is maintained at 100r / min-200r / min during the dropwise addition, the reaction container is placed in a constant temperature water bath, and the water bath is stirred at a temperature of 50°C-60°C and the reaction is continuously stirred for 4h-6h.
[0022] As a further solution of the present invention: in the step 4, the mixed solution in the reaction container is slowly dripped into a coagulation bath containing a calcium chloride solution, the dripping speed is controlled to be 10-15 drops per minute, the concentration of the calcium chloride solution is 2%-3%, the temperature of the coagulation bath is maintained at 25°C-40°C, the ambient temperature of the fermentation reaction is 30°C-40°C and the relative humidity is 65%-75%, and the fermentation time is 24h-48h.
[0023] As a further solution of the present invention: in the step five, the deionized water is repeatedly rinsed 3-5 times, and the amount of ionized water added each time is 2-3 times the volume of the composite material. The drying treatment adopts vacuum drying, the vacuum degree is set to 0.01MPa-0.1MPa, the drying temperature is 40℃-60℃, and the drying time is 12h-24h.
[0024] In addition, the present invention also provides an application of a composite material containing bentonite in desert control, and the application of the composite material in desert control includes the following process:
[0025] In the planned key windbreak and sand fixation areas, the bentonite composite material is mixed with the local sandy soil in a mass ratio of 1:5, and then the mixed material is laid on the windward slope of the sand dune with a thickness of 10 cm to form a windbreak and sand fixation cover layer with certain strength and stability to reduce the velocity of wind and sand flow and prevent the movement of sand dunes. In the key soil improvement and water conservation areas, the surface soil is first loosened to a depth of 20 cm, and the bentonite composite material is evenly spread on the loosened soil surface with a spreading amount of 800 g per square meter. Then the composite material is spread through shallow tillage. Mix it fully with the soil so that the composite material can penetrate into the soil to a certain depth to play its role in retaining water and improving soil fertility. In the areas where the above-mentioned windbreak and sand fixation and soil improvement and water conservation operations are completed, select vegetation varieties suitable for desert environment, such as Haloxylon ammodendron, Caragana korshinskii and Hippophae rhamnoides. Then, fill in part of the soil mixed with the bentonite composite material (the composite material and soil are mixed in a ratio of 1:6) in the planting pit, then plant the vegetation seedlings, fill in the remaining mixed soil and compact it appropriately to ensure that the roots of the seedlings are in close contact with the soil containing the composite material, thereby providing good soil conditions and water conservation support for vegetation growth.
[0026] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are:
[0027] 1. The present invention brings many significant advantages by synergistically compounding bentonite with natural high molecular polymers such as chitosan and adding plant fibers for modification. First, chitosan has many active functional groups and can interact with the surface of bentonite and water molecules through hydrogen bonds, electrostatic effects, etc. Its good biocompatibility and degradability not only reduce costs, but also make up for the defects of poor salt resistance and insufficient thermal stability of highly absorbent resins, and enhance water retention performance. Plant fibers are rich in cellulose, and their interwoven structure can be embedded in the composite system. When encountering external forces, such as wind and sand erosion, it can effectively disperse stress, significantly improve gel strength, and ensure the long-term effectiveness of the material in the desert environment. Moreover, chitosan can be converted into organic nutrients to nourish the soil after degradation. As time goes by, soil fertility is continuously improved, the durability of soil improvement effects is greatly improved, and the water retention and fertility of desert soil are comprehensively improved;
[0028] 2. The present invention effectively overcomes the performance defects of existing soil water-retaining materials by utilizing an innovative combination of bentonite-sodium alginate-mineral composite gel materials. Sodium alginate is a natural polysaccharide, and functional groups such as carboxyl groups on its molecular chain can form a large number of hydrogen bonds with water molecules, giving the material excellent water absorption and gel properties, solving the problem of low gel strength, and having good cost-effectiveness. The layered structure of the activated bentonite exposes more active sites due to the activation treatment, and the adsorption performance is greatly improved. It is closely combined with sodium alginate to synergistically enhance the adsorption and retention capacity of water and strengthen the water retention effect. The added minerals with slow-release properties can slowly release the trace elements inside under the action of soil moisture, microorganisms, etc. Over time, it continuously replenishes nutrients to the soil and improves soil fertility, thereby significantly improving the durability of soil improvement, ensuring that in scenarios such as desert control, the soil quality is stably and long-term improved to promote vegetation growth;
[0029] 3. The present invention prepares a composite water-retaining material by means of bentonite-lignin-microbial metabolites. Lignin is rich in functional groups such as phenolic hydroxyl groups and methoxy groups, and can be combined with bentonite through physical adsorption, hydrogen bonding, etc. Its own adsorption and water-retaining capacity cooperates with bentonite to greatly enhance the overall water-retaining performance of the material. The extracellular polysaccharides of microbial metabolites have a complex polysaccharide structure and can form a gel network in the system, further solving the problem of low gel strength. In the soil environment, over time, lignin is decomposed into small molecular organic matter under the action of microorganisms, and microbial metabolites also continuously release nutrients. These organic nutrients can improve the soil aggregate structure, increase soil aeration and water retention, continuously improve soil fertility, and improve the durability of soil improvement effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the method steps in an embodiment of the present invention. DETAILED DESCRIPTION
[0031] The specific embodiments of the present invention will be further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0032] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] Please see attached Figure 1 The present invention provides a method for preparing a composite material containing bentonite, the preparation method comprising the following specific steps:
[0034] Step 1, raw material preparation and pretreatment, select high-purity bentonite ore as the basic material, first grind the bentonite, activate the ground bentonite to improve its adsorption performance, soak the bentonite in a dilute hydrochloric acid solution and stir evenly, rinse repeatedly with clean water after stirring, and then put the activated bentonite into an oven for drying;
[0035] Select chitosan as a reactant, dissolve it in an acetic acid solution and mix it evenly for later use, collect the straw of plant fiber waste, wash it, dry it in the sun, and then crush it into powder for later use, select food-grade sodium alginate, dissolve it in warm water for later use, select montmorillonite powder and sieve it for later use, extract lignin from wood processing waste by alkaline extraction technology, soak it in a sodium hydroxide solution and stir it, filter it after soaking to obtain a filtrate containing lignin, add hydrochloric acid solution to the filtrate for acidification, filter and collect precipitated lignin after acidification, rinse it with clean water to neutrality, and then dry it for later use, cultivate Bacillus subtilis that can produce extracellular polysaccharides in LB medium, and collect the supernatant containing extracellular polysaccharides by centrifugation after the cultivation is completed;
[0036] Step 2, put all the bentonite into a reaction vessel with a stirring device, first add the dissolved chitosan solution, stir and mix until uniform during the addition process, ensure that the bentonite and chitosan are fully mixed, then add the prepared sodium alginate mixed solution, stir and mix until uniform during the addition process, ensure that the bentonite and sodium alginate are fully mixed, then add the purified lignin, stir and mix until uniform during the addition process, ensure that the bentonite and lignin are fully mixed;
[0037] Step 3: slowly add the plant fiber powder to the above-mentioned fully mixed reaction container, stir and mix until uniform during the addition process, ensure that the plant fiber powder is evenly dispersed in the system, and combine the plant fiber with the entire system. Subsequently, slowly add montmorillonite powder to the reaction container, stir and mix until uniform during the addition process, ensure that the montmorillonite powder is evenly dispersed in the system, and fully combine the montmorillonite powder with the entire system. Finally, slowly add the microbial metabolite extracellular polysaccharide solution to the reaction container, keep stirring during the addition process, and ensure that the extracellular polysaccharide is evenly dispersed in the industry system.
[0038] Step 4: under stirring conditions, add cross-linking agent glutaraldehyde dropwise to the reaction container. After the dropwise addition is completed, place the reaction container in a constant temperature water bath for water bath stirring to form stable chemical bonds between the components and enhance the gel strength and stability of the composite material. Under continuous stirring, slowly drop the mixed solution in the reaction container into a coagulation bath containing a calcium chloride solution. As the droplets gradually form gel beads in the coagulation bath, they are slowly fished out with a filter to avoid the gel beads from breaking. Then, a fermentation reaction is carried out. During the fermentation process, a series of complex chemical reactions will occur between the microbial metabolites and the bentonite and lignin, forming interactions such as chemical bonding and physical adsorption, thereby generating a composite water-retaining material.
[0039] Step 5: After the reaction is completed, the obtained composite material is repeatedly rinsed with deionized water to remove unreacted impurities and crosslinking agent residues, the rinsing liquid is discarded after rinsing, and the rinsed composite material is vacuum dried to obtain a bentonite-containing composite material.
[0040] In one embodiment of the present invention: in step one, the bentonite is ground by a ball mill for 4h-6h at a rotation speed of 300r / min-500r / min to make the particle size reach 200-500 mesh. The bentonite is activated by soaking the bentonite in a 10% dilute hydrochloric acid solution for 2h-3h with continuous stirring, then repeatedly rinsed with clean water until the pH value is 6.5-7.5, and then the activated bentonite is placed in an oven and dried at 60-80°C for 2h-3h for standby use.
[0041] In one embodiment of the present invention: in step 1, for chitosan, chitosan with a deacetylation degree of 80%-95% is selected, and it is dissolved in a 2%-5% acetic acid solution, and stirred at 100r / min-200r / min at room temperature until it is completely dissolved and then set aside;
[0042] Plant fiber waste straw needs to be crushed into 100-300 mesh powder for later use;
[0043] Sodium alginate is dissolved in warm water at a temperature of 40°C-50°C, with a mass ratio of sodium alginate to warm water of 1:10-15, and stirred at 150r / min-250r / min until dissolved and set aside;
[0044] Select montmorillonite powder with a purity of 90%-95%, sieve it to 100-300 mesh and set aside;
[0045] Soak the lignin in a 10%-15% sodium hydroxide solution at 80°C-90°C for 3h-5h with stirring, filter after the soaking to obtain a filtrate containing lignin, add 1 mol / L hydrochloric acid solution to the filtrate for acidification to reduce the pH value to 2-3, filter and collect the precipitated lignin, rinse with clean water until neutral, and then dry at 50°C-60°C for use;
[0046] Bacillus subtilis capable of producing extracellular polysaccharides is cultured in LB medium, and cultured in a shaking incubator at 30°C-37°C and 150r / min-200r / min for 24h-48h. After the culture is completed, the supernatant containing the extracellular polysaccharides is collected and used after centrifugation at 5000r / min-8000r / min for 10min-15min.
[0047] In one embodiment of the present invention: in step 2, the amount of chitosan solution added is added according to the mass ratio of bentonite to chitosan solution of 1:2-4, and during the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30min-60min. The amount of sodium alginate mixed solution added is added according to the mass ratio of bentonite to sodium alginate of 2:3-5. During the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30min-60min. The amount of lignin added is added according to the mass ratio of bentonite to lignin of 3-5:2. During the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30-60 minutes.
[0048] In one embodiment of the present invention: in step three, the amount of plant fiber powder added is 10%-15% of the total mass of the system, stirring is maintained during the addition process, the stirring speed is 150r / min-250r / min, and the stirring reaction is carried out for 30min-60min. The amount of montmorillonite powder added accounts for 15%-18% of the total mass of the system, stirring is continued during the addition process, the stirring speed is controlled to be 150r / min-250r / min, and stirring is continued for 30min-60min. The amount of extracellular polysaccharide added accounts for 20%-23% of the total mass of the system, stirring is continued during the addition process, the stirring speed is controlled to be 150r / min-250r / min, and the stirring reaction is carried out for 30min-60min.
[0049] In one embodiment of the present invention: in step 4, the amount of glutaraldehyde added is 1%-1.5% of the total mass of the system, the stirring speed is maintained at 100r / min-200r / min during the dropwise addition, the reaction container is placed in a constant temperature water bath, and the water bath is stirred at a temperature of 50°C-60°C for 4h-6h.
[0050] In one embodiment of the present invention: in step 4, the mixed solution in the reaction container is slowly dripped into a coagulation bath containing a calcium chloride solution, the dripping rate is controlled to be 10-15 drops per minute, the concentration of the calcium chloride solution is 2%-3%, the temperature of the coagulation bath is maintained at 25°C-40°C, the ambient temperature of the fermentation reaction is 30°C-40°C and the relative humidity is 65%-75%, and the fermentation time is 24h-48h.
[0051] In one embodiment of the present invention: in step five, the deionized water is repeatedly rinsed 3-5 times, and the amount of ionized water added each time is 2-3 times the volume of the composite material. The drying treatment adopts vacuum drying, the vacuum degree is set to 0.01MPa-0.1MPa, the drying temperature is 40℃-60℃, and the drying time is 12h-24h.
[0052] In one embodiment of the present invention: in step one, after the bentonite is activated, the method further includes the step of performing a secondary treatment on the activated bentonite, placing the activated and dried bentonite in a microwave field for microwave irradiation treatment, wherein the microwave power is set to 500W-800W, and the irradiation time is 10min-20min. Through microwave irradiation, the crystal structure of the bentonite can be further changed, and the chemical bonds inside the bentonite can be fine-tuned, thereby increasing its specific surface area and the number of active sites, so that in the subsequent composite reaction with other substances, it can more effectively adsorb and combine with other reactants, further enhance the comprehensive performance of the composite material, and improve its water retention, soil improvement and other effects in application scenarios such as desert control.
[0053] In one embodiment of the present invention: in step 2, after chitosan solution, sodium alginate mixed solution and lignin are added in sequence and stirred and mixed evenly, nano titanium dioxide powder is added to the reaction container, the amount of nano titanium dioxide powder added is 3%-5% of the total mass of the system, and the stirring speed is 150r / min-200r / min for 30min-45min during the adding process to ensure that it is evenly dispersed in the system. Nano titanium dioxide has good photocatalytic properties. When the composite material is applied to a desert environment, ultraviolet rays in natural sunlight can be used to stimulate its photocatalytic activity to generate free radicals with strong oxidizing properties. These free radicals can decompose some organic pollutants that may exist in desert soil, and at the same time help to improve the living environment of soil microorganisms, promote the growth and reproduction of beneficial microorganisms, and indirectly improve soil fertility and the improvement effect of the composite material on desert soil. The high chemical stability of the nano titanium dioxide itself also helps to enhance the overall stability of the composite material.
[0054] In one embodiment of the present invention: in step 3, after adding plant fiber powder, montmorillonite powder and extracellular polysaccharide solution of microbial metabolites into the reaction container and completing the corresponding stirring reaction, a bioactive additive is added to the system, the bioactive additive is composed of equal amounts of plant growth hormone and microbial agent, the plant growth hormone is indoleacetic acid, and the microbial agent is a composite microbial agent with nitrogen fixation, phosphorus solubilization and potassium solubilization functions, the amount of the bioactive additive added is 5%-8% of the total mass of the system, and the stirring speed is 120r / min-180r / min for 40min-50min during the adding process to ensure that it is evenly dispersed in the system, the plant growth hormone can stimulate the germination of desert plant seeds and the growth of seedlings, and improve the survival rate of plants in harsh desert environments, and the composite microbial agent can play the role of nitrogen fixation, phosphorus solubilization, potassium solubilization, etc. in the soil, increase the effective nutrient content in the soil, and synergize with the water retention and soil improvement properties of the composite material itself, significantly improve the desert control effect, and accelerate the recovery of desert vegetation.
[0055] In one embodiment of the present invention: in step 4, after the mixed solution in the reaction container is slowly dripped into a coagulation bath containing a calcium chloride solution to form gel beads, a step of surface modification of the gel beads is also included, and the specific operation is: soaking the prepared gel beads in a solution containing polydopamine, the concentration of the polydopamine solution is 0.5%-1.5%, the soaking time is 2h-4h, and slight stirring is maintained during the soaking process to allow the surface of the gel beads to fully contact the solution. Polydopamine can self-polymerize on the surface of the gel beads to form a uniform polydopamine coating, and the coating has good adhesion and biocompatibility. On the one hand, it can enhance the ability of the gel beads to resist wind and sand wear in the desert environment, prevent the surface of the gel beads from being damaged by wind and sand erosion, thereby maintaining its complete water retention and soil improvement functions. On the other hand, its biocompatibility is conducive to the attachment and growth of microorganisms on the surface of the gel beads in the subsequent desert control process, promotes the establishment of a desert soil microbial ecosystem, and further enhances the soil improvement effect.
[0056] In one embodiment of the present invention: in step 4, after the mixed solution in the reaction container is slowly dripped into a coagulation bath containing a calcium chloride solution to form gel beads, the gel beads are synergistically treated with desert plant seeds for desert control, and the specific operation is as follows:
[0057] First, plant seeds suitable for growing in desert environments, such as Haloxylon ammodendron, Caragana korshinskii and Hippophae rhamnoides, are selected, and the gel beads are mixed evenly with the selected plant seeds at a mass ratio of 3-5:1, and then placed in a special slow-release container. The slow-release container has certain air permeability and water permeability, and its material is a biodegradable polymer material, polylactic acid;
[0058] Then, the slow-release container containing the mixture of gel beads and plant seeds is buried 3cm-5cm below the desert surface. In the desert environment, the gel beads play multiple roles: on the one hand, the gel beads have excellent water retention properties and can absorb and store the scarce precipitation in the desert and water vapor in the air, slowly releasing moisture to provide a continuous and stable supply of water for the germination of plant seeds and the growth of seedlings, effectively improving the germination rate of plant seeds in the desert; on the other hand, over time, the gel beads will gradually decompose and release the various nutrients they contain, such as microbial metabolites added during the preparation process, nutrients produced by the decomposition of lignin, etc. These nutrients can provide the necessary nutrient support for the growth of plant seedlings and promote the growth and development of plants in the desert.
[0059] An application of a composite material containing bentonite in desert control, wherein the application of the composite material in desert control includes the following processes:
[0060] In the planned key windbreak and sand fixation areas, the bentonite composite material is mixed with the local sandy soil in a mass ratio of 1:5, and then the mixed material is laid on the windward slope of the sand dune with a thickness of 10 cm to form a windbreak and sand fixation cover layer with certain strength and stability to reduce the velocity of wind and sand flow and prevent the movement of sand dunes. In the key soil improvement and water conservation areas, the surface soil is first loosened to a depth of 20 cm, and the bentonite composite material is evenly spread on the loosened soil surface with a spreading amount of 800 g per square meter. Then the composite material is spread through shallow tillage. Mix it fully with the soil so that the composite material can penetrate into the soil to a certain depth to play its role in retaining water and improving soil fertility. In the areas where the above-mentioned windbreak and sand fixation and soil improvement and water conservation operations are completed, select vegetation varieties suitable for desert environment, such as Haloxylon ammodendron, Caragana korshinskii and Hippophae rhamnoides. Then, fill in part of the soil mixed with the bentonite composite material (the composite material and soil are mixed in a ratio of 1:6) in the planting pit, then plant the vegetation seedlings, fill in the remaining mixed soil and compact it appropriately to ensure that the roots of the seedlings are in close contact with the soil containing the composite material, thereby providing good soil conditions and water conservation support for vegetation growth.
[0061] Example 1, please refer to the attached Figure 1, high-purity bentonite ore was selected as the basic material, and it was ground in a ball mill for 6 hours at a speed of 500r / min to a particle size of 500 mesh. The ground bentonite was then immersed in a 10% dilute hydrochloric acid solution for 3 hours with constant stirring, and then repeatedly rinsed with clean water until the pH value was 7.5. Put the activated bentonite into an oven and dry it at 80℃ for 3h for later use. Select chitosan with a deacetylation degree of 95%, dissolve it in a 5% acetic acid solution, stir it at 200r / min at room temperature until it is completely dissolved for later use. Collect the straw of plant fiber waste, wash it, dry it in the sun, and crush it into 300 mesh powder for later use. Select montmorillonite powder with a purity of 95%, sieve it to 300 mesh and set it aside. Soak lignin in 15% sodium hydroxide solution, soak it at 90℃ for 5h and stir it. After soaking, filter it to obtain a filtrate containing lignin. Add 1mol / L hydrochloric acid solution to the filtrate for acidification to reduce the pH value to 3. Filter and collect the precipitated lignin, and then rinse it with clean water. to neutral, then dried at 60°C for later use, culture Bacillus subtilis capable of producing extracellular polysaccharides in LB medium, culture in a shaking incubator at 37°C and 200r / min for 48h, centrifuge at 8000r / min for 15min after the culture, collect the supernatant containing extracellular polysaccharides for later use, then put all the bentonite into a reaction vessel with a stirring device, first add the dissolved chitosan solution in a ratio of 1:4 to the mass ratio of bentonite to chitosan solution, control the stirring speed to 300r / min during the addition process, and the stirring time to 60min to ensure that the bentonite and chitosan are fully mixed, then add the prepared sea alginate in a ratio of 2:5 to the mass ratio of bentonite to sodium alginate The sodium alginate mixture was added, and the stirring speed was controlled to be 300r / min during the addition process, and the stirring time was 60min to ensure that the bentonite and the sodium alginate were fully mixed. Then, the purified lignin was added according to the mass ratio of bentonite to lignin of 5:2. The stirring speed was controlled to be 300r / min during the addition process, and the stirring time was 60 minutes to ensure that the bentonite and the lignin were fully mixed. In the above-mentioned fully mixed reaction container, the plant fiber powder was slowly added thereto, and the addition amount was 15% of the total mass of the system. Stirring was maintained during the addition process, and the stirring speed was 250r / min. The stirring reaction was carried out for 60min to ensure that the plant fiber powder was evenly dispersed in the system, so that the plant fiber and the entire The system was combined, and then montmorillonite powder was slowly added to the reaction vessel, and its addition amount accounted for 18% of the total mass of the system. Stirring was continued during the addition process, and the stirring speed was controlled to 250r / min. Stirring was continued for 60min to ensure that the montmorillonite powder was evenly dispersed in the system and that the montmorillonite powder was fully combined with the entire system. Finally, the microbial metabolite extracellular polysaccharide solution was slowly added to the reaction vessel, and its addition amount accounted for 23% of the total mass of the system. Stirring was continued during the addition process, and the stirring speed was controlled to 250r / min. Stirring reaction was continued for 60min to ensure that the extracellular polysaccharide was evenly dispersed in the system. Under stirring conditions, crosslinking agent glutaraldehyde was added dropwise to the reaction vessel, and its addition amount was 1.5%, keep the stirring speed at 200r / min during the dropping process. After the dropping is completed, place the reaction container in a constant temperature water bath, and continue to stir and react at a temperature of 60°C for 6h to form stable chemical bonds between the components and enhance the gel strength and stability of the composite material. Under continuous stirring, slowly drip the mixed solution in the reaction container into a coagulation bath containing calcium chloride solution, control the dripping speed at 15 drops per minute, the concentration of calcium chloride solution is 3%, and the temperature of the coagulation bath is maintained at 40°C. As the droplets gradually form gel beads in the coagulation bath, slowly remove them with a filter to avoid coagulation. The beads are broken and then fermented. During the fermentation process, a series of complex chemical reactions will occur between the microbial metabolites and the bentonite and lignin, forming chemical bonding and physical adsorption interactions, thereby generating a composite water-retaining material. After the reaction is completed, the obtained composite material is repeatedly rinsed with deionized water for 5 times, and the amount of deionized water added each time is 3 times the volume of the composite material. After rinsing, the rinse liquid is poured out and the rinsed composite material is vacuum dried. The vacuum degree is set to 0.1MPa, the drying temperature is 60℃, and the drying time is 24h to obtain a composite material containing bentonite.
[0062] Example 2, please refer to the attached Figure 1, select high-purity bentonite ore as the basic material, grind it with a ball mill for 4 hours, with a speed of 300r / min, so that the particle size reaches 200 mesh, then soak the ground bentonite in 10% dilute hydrochloric acid solution for 2 hours and stir continuously, then rinse it repeatedly with clean water until the pH value is 6.5, then put the activated bentonite into an oven, dry it at 60°C for 2 hours for use, select chitosan with a deacetylation degree of 80%, dissolve it in 2% acetic acid solution, stir it at 100r / min at room temperature until it is completely dissolved for use, collect the straw of plant fiber waste, wash it, dry it in the sun, and crush it into 100 mesh powder for use, select montmorillonite powder with a purity of 90%, sieve it to 100 mesh and set it aside, soak lignin in 10% sodium hydroxide solution , soak at 80 ° C for 3 hours and stir, filter after the soaking to obtain a filtrate containing lignin, add 1 mol / L hydrochloric acid solution to the filtrate for acidification, reduce the pH value to 2, filter and collect the precipitated lignin, rinse with clean water to neutrality, and then dry at 50 ° C for use, culture Bacillus subtilis that can produce extracellular polysaccharides in LB medium, shake and culture at 30 ° C and 150 r / min for 24 hours, centrifuge at 5000 r / min for 10 minutes after the culture, collect the supernatant containing extracellular polysaccharides for use, then put all the bentonite into a reaction vessel with a stirring device, first add the dissolved chitosan solution according to the mass ratio of bentonite to chitosan solution of 1:2, and control the stirring speed to 200 during the addition process. r / min, stirring time is 30min, ensure that bentonite and chitosan are fully mixed, then add the prepared sodium alginate mixture according to the mass ratio of bentonite to sodium alginate of 2:3, control the stirring speed to 200r / min during the addition process, stirring time is 30min, ensure that bentonite and sodium alginate are fully mixed, then add purified lignin according to the mass ratio of bentonite to lignin of 3:2, control the stirring speed to 200r / min during the addition process, stirring time is 30 minutes, ensure that bentonite and lignin are fully mixed, slowly add plant fiber powder into the above-mentioned fully mixed reaction vessel, the addition amount is 10% of the total mass of the system, keep stirring during the addition process, stirring speed The stirring speed is 150r / min, and the reaction is stirred for 30min to ensure that the plant fiber powder is evenly dispersed in the system, so that the plant fiber is combined with the entire system. Subsequently, montmorillonite powder is slowly added to the reaction vessel, and the addition amount accounts for 15% of the total mass of the system. Stirring is continued during the addition process, and the stirring speed is controlled to be 150r / min. Stirring is continued for 30min to ensure that the montmorillonite powder is evenly dispersed in the system, so that the montmorillonite powder is fully combined with the entire system. Finally, the microbial metabolite extracellular polysaccharide solution is slowly added to the reaction vessel, and the addition amount accounts for 20% of the total mass of the system. Stirring is continued during the addition process, and the stirring speed is controlled to be 150r / min. Stirring reaction is carried out for 30min to ensure that the extracellular polysaccharide is evenly dispersed in the system. Under stirring conditions,The cross-linking agent glutaraldehyde was added dropwise to the reaction container, and the addition amount was 1% of the total mass of the system. The stirring speed was maintained at 100 r / min during the dropwise addition. After the dropwise addition was completed, the reaction container was placed in a constant temperature water bath, and the reaction was continuously stirred at a temperature of 50°C for 4 hours to form stable chemical bonds between the components and enhance the gel strength and stability of the composite material. Under continuous stirring, the mixed solution in the reaction container was slowly dripped into a coagulation bath containing a calcium chloride solution, and the dripping speed was controlled to 10 drops per minute. The concentration of the calcium chloride solution was 2%, and the temperature of the coagulation bath was maintained at 25°C. As the droplets gradually formed gel beads in the coagulation bath, , slowly scoop it out with a filter to avoid the gel beads from breaking, and then ferment. During the fermentation process, a series of complex chemical reactions will occur between the microbial metabolites and the bentonite and lignin, forming chemical bonding and physical adsorption interactions, thereby generating a composite water-retaining material. After the reaction, the obtained composite material is repeatedly rinsed with deionized water for 3 times, and the amount of deionized water added each time is 2 times the volume of the composite material. After rinsing, the rinse liquid is poured out, and the rinsed composite material is vacuum dried, with the vacuum degree set to 0.01MPa, the drying temperature to 40℃, and the drying time to 12h, to obtain a composite material containing bentonite. ,
[0063] Although the present invention is disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a composite material containing bentonite, characterized in that: The preparation method comprises the following specific steps: Step 1, raw material preparation and pretreatment, select high-purity bentonite ore as the basic material, first grind the bentonite, activate the ground bentonite, soak the bentonite in a dilute hydrochloric acid solution and stir evenly, rinse repeatedly with clean water after stirring, and then put the activated bentonite into an oven for drying; Select chitosan as a reactant, dissolve it in an acetic acid solution and mix it evenly for later use, collect the straw of plant fiber waste, wash it, dry it in the sun, and then crush it into powder for later use, select food-grade sodium alginate, dissolve it in warm water for later use, select montmorillonite powder and sieve it for later use, extract lignin from wood processing waste by alkaline extraction technology, soak it in a sodium hydroxide solution and stir it, filter it after soaking to obtain a filtrate containing lignin, add hydrochloric acid solution to the filtrate for acidification, filter and collect precipitated lignin after acidification, rinse it with clean water to neutrality, and then dry it for later use, cultivate Bacillus subtilis that can produce extracellular polysaccharides in LB medium, and collect the supernatant containing extracellular polysaccharides by centrifugation after the cultivation is completed; Step 2: Put all the bentonite into a reaction vessel with a stirring device, first add the dissolved chitosan solution, stir and mix until uniform during the addition process, then add the prepared sodium alginate mixed solution, stir and mix until uniform during the addition process, then add the purified lignin, stir and mix until uniform during the addition process; Step 3: slowly add the plant fiber powder to the above-mentioned fully mixed reaction container, stirring and mixing until uniform during the addition process, then slowly add the montmorillonite powder to the reaction container, stirring and mixing until uniform during the addition process, and finally, slowly add the microbial metabolite extracellular polysaccharide solution to the reaction container, stirring during the addition process; Step 4: under stirring conditions, add crosslinking agent glutaraldehyde dropwise into the reaction container. After the dropwise addition is completed, place the reaction container in a constant temperature water bath for water bath stirring. Under continuous stirring, slowly drop the mixed solution in the reaction container into a coagulation bath containing a calcium chloride solution. As the droplets gradually form gel beads in the coagulation bath, the gel beads are slowly removed with a filter to prevent the gel beads from breaking, and then a fermentation reaction is performed to generate a composite water-retaining material. Step 5: After the reaction is completed, the obtained composite material is repeatedly rinsed with deionized water, the rinsing liquid is discarded after rinsing, and the rinsed composite material is subjected to vacuum drying treatment to obtain a composite material containing bentonite.
2. The method for preparing a composite material containing bentonite according to claim 1, characterized in that: In the step 1, the bentonite is ground by a ball mill for 4h-6h at a rotation speed of 300r / min-500r / min to make the particle size reach 200-500 meshes. The bentonite is activated by soaking the bentonite in a 10% dilute hydrochloric acid solution for 2h-3h with continuous stirring, then repeatedly rinsed with clean water until the pH value is 6.5-7.5, and then the activated bentonite is placed in an oven and dried at 60-80°C for 2h-3h for standby use.
3. The method for preparing a composite material containing bentonite according to claim 1, characterized in that: In the step 1, for chitosan, chitosan with a deacetylation degree of 80%-95% is selected, and the chitosan is dissolved in a 2%-5% acetic acid solution, and stirred at 100r / min-200r / min at room temperature until completely dissolved for later use; Plant fiber waste straw needs to be crushed into 100-300 mesh powder for later use; Sodium alginate is dissolved in warm water at a temperature of 40°C-50°C, with a mass ratio of sodium alginate to warm water of 1:10-15, and stirred at 150r / min-250r / min until dissolved and set aside; Select montmorillonite powder with a purity of 90%-95%, sieve it to 100-300 mesh and set aside; The lignin is soaked in a 10%-15% sodium hydroxide solution at 80°C-90°C for 3h-5h and stirred. After the soaking, the filtrate containing the lignin is filtered to obtain a filtrate, and a 1 mol / L hydrochloric acid solution is added to the filtrate for acidification to reduce the pH value to 2-3. The precipitated lignin is collected by filtering, and then rinsed with clean water until neutral, and then dried at 50°C-60°C for use; Bacillus subtilis capable of producing extracellular polysaccharides is cultured in LB medium, and cultured in a shaking incubator at 30°C-37°C and 150r / min-200r / min for 24h-48h. After the culture is completed, the supernatant containing the extracellular polysaccharides is collected and used after centrifugation at 5000r / min-8000r / min for 10min-15min.
4. The method for preparing a composite material containing bentonite according to claim 1, characterized in that: In the step 2, the amount of chitosan solution added is added according to the mass ratio of bentonite to chitosan solution of 1:2-4, and during the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30min-60min. The amount of sodium alginate mixed solution added is added according to the mass ratio of bentonite to sodium alginate of 2:3-5. During the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30min-60min. The amount of lignin added is added according to the mass ratio of bentonite to lignin of 3-5:
2. During the addition process, the stirring speed is controlled to be 200r / min-300r / min, and the stirring time is 30-60 minutes.
5. The method for preparing a composite material containing bentonite according to claim 1, characterized in that: In the step three, the amount of plant fiber powder added is 10%-15% of the total mass of the system, stirring is maintained during the addition process, the stirring speed is 150r / min-250r / min, and the stirring reaction is carried out for 30min-60min. The amount of montmorillonite powder added accounts for 15%-18% of the total mass of the system, stirring is continued during the addition process, the stirring speed is controlled to be 150r / min-250r / min, and stirring is continued for 30min-60min. The amount of extracellular polysaccharide added accounts for 20%-23% of the total mass of the system, stirring is continued during the addition process, the stirring speed is controlled to be 150r / min-250r / min, and the stirring reaction is carried out for 30min-60min.
6. The method for preparing a composite material containing bentonite according to claim 1, characterized in that: In the step 4, the amount of glutaraldehyde added is 1%-1.5% of the total mass of the system. During the dropwise addition, the stirring speed is maintained at 100r / min-200r / min. The reaction vessel is placed in a constant temperature water bath and stirred in the water bath at a temperature of 50°C-60°C for 4h-6h.
7. The method for preparing a composite material containing bentonite according to claim 1, characterized in that: In the step 4, the mixed solution in the reaction container is slowly dripped into a coagulation bath containing a calcium chloride solution, the dripping speed is controlled to be 10-15 drops per minute, the concentration of the calcium chloride solution is 2%-3%, the temperature of the coagulation bath is maintained at 25°C-40°C, the ambient temperature of the fermentation reaction is 30°C-40°C and the relative humidity is 65%-75%, and the fermentation time is 24h-48h.
8. The method for preparing a composite material containing bentonite according to claim 1, characterized in that: In the step 5, the deionized water is repeatedly rinsed 3-5 times, and the amount of deionized water added each time is 2-3 times the volume of the composite material. The drying treatment adopts vacuum drying, and the vacuum degree is set to 0.01MPa-0.1MPa, the drying temperature is 40℃-60℃, and the drying time is 12h-24h.
9. An application of a bentonite-containing composite material applicable to the preparation method of a bentonite-containing composite material according to any one of claims 1 to 8 in desert control, characterized in that: The application of the composite material in desert control includes the following processes: In the planned key windbreak and sand fixation areas, the bentonite composite material is mixed with the local sandy soil in a mass ratio of 1:5, and then the mixed material is laid on the windward slope of the sand dune with a thickness of 10 cm to form a windbreak and sand fixation cover layer with certain strength and stability to reduce the velocity of wind and sand flow and prevent the movement of sand dunes. In the key soil improvement and water conservation areas, the surface soil is first loosened to a depth of 20 cm, and the bentonite composite material is evenly spread on the loosened soil surface with a spreading amount of 800 g per square meter. Then the composite material is spread through shallow tillage. Mix it fully with the soil so that the composite material can penetrate into the soil to a certain depth to play its role in retaining water and improving soil fertility. In the areas where the above-mentioned windbreak and sand fixation and soil improvement and water conservation operations are completed, select vegetation varieties suitable for desert environment, such as Haloxylon ammodendron, Caragana korshinskii and Hippophae rhamnoides. Then, fill in part of the soil mixed with the bentonite composite material (the composite material and soil are mixed in a ratio of 1:6) in the planting pit, then plant the vegetation seedlings, fill in the remaining mixed soil and compact it appropriately to ensure that the roots of the seedlings are in close contact with the soil containing the composite material, thereby providing good soil conditions and water conservation support for vegetation growth.
Citation Information
Patent Citations
Compound organic fertilizer and preparation method thereof
CN114478121A
Modified plant fiber-mineral composite soil improvement material and preparation method thereof
CN114538881A
Plant fiber bonded soil improvement composite material as well as preparation method and application thereof
CN114806594A
Original soil improver, preparation method and soil improvement method
CN117821076A
Cited By
Green degradable porous oil absorption material and preparation method thereof
CN121155516A